2011
DOI: 10.12693/aphyspola.119.602
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Orbit Coupling in n-Type PbTe/PbEuTe Quantum Wells

Abstract: Magnetoresistance measurements were performed on an n-type PbTe/PbEuTe quantum well and weak antilocalization effects were observed. This indicates the presence of spin-orbit coupling phenomena and we showed that the Rashba effect is the main mechanism responsible for this spin-orbit coupling. Using the model developed by Iordanskii et al., we fitted the experimental curves and obtained the inelastic and spin-orbit scattering times. Thus we could compare the zero field energy spin-splitting predicted by the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…These observations point to strong Rashba spin−orbit interaction and asymmetric confinement potentials in the PbTe quantum dots. 26 This is consistent with predicted small Dresselhaus SOI in PbTe due to its inversion-symmetric rocksalt crystalline structure 38 and large Rashba SOI, as measured in PbTe quantum wells. 7 Moreover, g-factor anisotropy was predicted for [100] and [111] PbTe quantum wells, 13 where the authors included the contributions of wave function barrier penetration, confinement energy shift, and interface SO interaction in their calculations of the quantum well g-factors.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…These observations point to strong Rashba spin−orbit interaction and asymmetric confinement potentials in the PbTe quantum dots. 26 This is consistent with predicted small Dresselhaus SOI in PbTe due to its inversion-symmetric rocksalt crystalline structure 38 and large Rashba SOI, as measured in PbTe quantum wells. 7 Moreover, g-factor anisotropy was predicted for [100] and [111] PbTe quantum wells, 13 where the authors included the contributions of wave function barrier penetration, confinement energy shift, and interface SO interaction in their calculations of the quantum well g-factors.…”
supporting
confidence: 84%
“…26 This is consistent with predicted small Dresselhaus SOI in PbTe due to its inversion-symmetric rocksalt crystalline structure 38 and large Rashba SOI, as measured in PbTe quantum wells. 7 Moreover, g-factor anisotropy was predicted for [100] and [111] PbTe quantum wells, 13 where the authors included the contributions of wave function barrier penetration, confinement energy shift, and interface SO interaction in their calculations of the quantum well g-factors. Furthermore, they found that a confining mesoscopic potential renormalizes the g-factor through Rashba SOI.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…A simple realization of this can be seen (see Fig. 3 ) by considering the minimal quadratic Hamiltonian with the linear Rashba contribution 26 where is the Rashba coefficient and determines the robustness of the splitting. The related dispersion is of the form : ε = ħ 2 k 2 /2 m * ± λ R k ; the splitting is therefore 2 λ R k , where k is the in-plane wave vector given by .…”
Section: Resultsmentioning
confidence: 99%
“…Fine control of the electron density in PbTe/PbEuTe quantum wells made possible the observation of the integer quantum Hall effect 11,12 and of the conductance quantization in constricted samples. 13 The effects of localization and antilocalization were investigated in n-type 14 and p-type 15 doped Pb 1−x Eu x Te layers and an enhancement of the thermoelectric power was observed in PbTe/PbEuTe multiquantum wells. 1 In principle, the lead salts can be easily doped by controlling the stoichiometric deviation, i.e., p-type ͑n-type͒ material is obtained from a chalcogen-rich ͑metal-rich͒ growth regime.…”
Section: Introductionmentioning
confidence: 99%